An efficient method to clone TAL effector genes from Xanthomonas oryzae using Gibson assembly. (15th August 2019) - Li, Chenhao; Ji, Chonghui; Huguet‐Tapia, José C.; White, Frank F.; Dong, Hansong; Yang, Bing
Summary: Transcription Activator‐Like effectors (TALes) represent the largest family of type III effectors among pathogenic bacteria and play a critical role in the process of infection. Strains of Xanthomonas oryzae pv. oryzae (Xoo) and some strains of other Xanthomonas pathogens contain large numbers of TALe genes. Previous techniques to clone individual or a complement of TALe genes through conventional strategies are inefficient and time‐consuming due to multiple genes (up to 29 copies) in a given genome, and technically challenging due to the repetitive sequences (up to 33 nearly identical 102‐nucleotide repeats) of individual TALe genes. Thus, only a limited number of TALe genes have been molecularly cloned and characterized, and the functions of most TALe genes remain unknown. Here, we present an easy and efficient cloning technique to clone TALe genes selectively through in vitro homologous recombination and single‐strand annealing, and demonstrate the feasibility of this approach with four different Xoo strains. Based on the Gibson assembly strategy, two complementary vectors with scaffolds that can preferentially capture all TALe genes from a pool of genomic fragments were designed. Both vector systems enabled cloning of a full complement of TALe genes from each of four Xoo strains and functional analysis of individual TALes in rice in approximately 1 month compared to 3 months by previously used methods. The results demonstrate a robust tool to advance TALe biology and a potential for broad usage of this approach to clone multiple copies of highly competitive DNA elements in any genome of interest.